Urban Agricultural Development For Food Security at the Time of Covid-19 Pandemies in Indonesia - Sutrisna, Nana (Sumatra Journal of Disaster, Geography and Geography Education, 2020)
Corona virus pandemic (Covid-19) threatens the lives of people in the world and has an impact on the economy of society, including in Indonesia, both in the industrial, trade and agriculture sectors. In the agricultural sector, food security is the main thing that must receive attention from the government because it can disrupt national stability. One effort that can be done is the development of urban agriculture. Urban agriculture can improve local food security and quality of agricultural products. The combination of innovative urban agriculture such as vertical garden, hydroponic, and vertiminaponic cultivation systems at various scales (small, medium, and commercial) is able to support three dimensions of food security, namely food availability, food access, and food utilization. On a small and medium scale urban agriculture is able to produce a number of vegetables for the local market. On a medium and commercial scale it can be developed to complement national or even global needs. Urban innovative agriculture also has the potential to contribute to food stability, namely reducing dependence on long and poorly developed food value chains, from rural producers to urban consumers. On that basis, innovative urban agriculture has paved the way to the second green revolution, ensuring availability and maintaining food security during the COVID-19 pandemic in Indonesia. However, in its development requires cooperation from all parties, including farmers, government, surrounding communities, entrepreneurs, educational institutions, and other parties for sustainability.